Attitudes and Behaviors Toward face Mask Use during the COVID-19 Pandemic: A Cross-Sectional Study from Punjab, Pakistan. - Liaqat , Aisha; Shahid, Wali Ullah; Zunaira Tahir; Samia Shaukat; Syeda Kaainaat Binte Waheed; Suffian Habib; Bisma Mushtaq (International Journal of Endorsing Health Science Research, 2025)
Background: Face masks are a core non-pharmaceutical intervention to limit SARS-CoV-2 transmission, yet public attitudes and everyday practices vary widely. Understanding who wears masks, how they are worn, and why people comply or resist can inform targeted public health strategies. Methodology: A descriptive cross-sectional online survey was conducted between November 2020 and March 2021. Adults aged ≥18 years with at least secondary education were eligible. The questionnaire included demographics, COVID-19 history, attitudes, and behaviors. Reliability of Likert-type scales was acceptable (Cronbach’s α = 0.78). Descriptive statistics, t-tests, and chi-square tests were applied using SPSS v22, with effect sizes reported (Cohen’s d, Cramer’s V). A significance level of p < 0.05 was applied. Results: Of 495 respondents (201 males; 294 females), females reported higher regular mask use (85.0% vs. 66.7%, p = 0.001) and greater endorsement of correct wearing (covering nose, mouth, chin). Males more often reported barriers (e.g., “hassle,” reduced confidence), skepticism about effectiveness, and improper wearing (e.g., mouth/chin only). Significant but small-to-moderate effects were observed across multiple items (typical d ≈ 0.2–0.36; Cramer’s V up to 0.39 for employment status). Conclusion: Clear gender differences exist in mask-related attitudes and behaviors. Tailored, gender-sensitive communication and low-cost access strategies may increase adherence, particularly among men. Findings can guide behaviorally informed interventions for future respiratory outbreaks.